Transzonal projections: Essential structures mediating intercellular communication in the mammalian ovarian follicle - Clarke, Hugh J. (Molecular reproduction and development, 2022)
The development of germ cells relies on contact and communication with neighboring somatic cells that provide metabolic support and regulatory signals. In females, contact is achieved through thin cytoplasmic processes that project from follicle cells surrounding the oocyte, extend through an extracellular matrix (ECM) that lies between them, and reach its surface. In mammals, the ECM is termed the zona pellucida and the follicular cell processes are termed transzonal projections (TZPs). TZPs become detectable when the zona pellucida is laid down during early folliculogenesis and subsequently increase in number as oocyte growth progresses. They then rapidly disappear at the time of ovulation, permanently breaking germ‐soma contact. Here we review the life cycle and functions of the TZPs. We begin with an overview of the morphology and cytoskeletal structure of TZPs, in the context of actin‐ and tubulin‐based cytoplasmic processes in other cell types. Next, we review the roles played by TZPs in mediating progression through successive stages of oocyte development. We then discuss two mechanisms that may generate TZPs—stretching at pre‐existing points of granulosa cell‐oocyte contact and elaboration of new processes that push through the zona pellucida—as well as gene products implicated in their formation or function. Finally, we describe the signaling pathways that cause TZPs to be retracted in response to signals that also trigger meiotic maturation and ovulation of the oocyte. The principles and mechanisms that govern TZP behavior may be relevant to understanding communication between physically separated cells in other physiological contexts.